Business Unit "Mooghurt" Academic Community Biology Department FMIPA Universitas Negeri Padang - Syamsurizal Syamsurizal; Linda Advinda; Resti Fevria; M Maizirwan (Pelita Eksakta, 2018)
Abstract - Science and Technology Program for Entrepreneurship and Campus Innovation (IbKIK) involves a number of experienced lecturers from various disciplines. IbKIK carries out guidance to prospective entrepreneurs / novice entrepreneurs (students) through business management training and a number of other creative activities to produce new entrepreneurs who are independent in science and technology based. The form of new entrepreneurship offered is the production of fermented cow's milk which is named the "Mooghurt" Business Unit of the Biology Department of the Faculty of Mathematics and Natural Sciences UNP. Mooghurt is designed primarily to generate and develop the entrepreneurial spirit of students in the Biology Department at FMIPA UNP. The activities that have been carried out are the manufacture of moquette with a taste of plan (original, pineapple, starwbery and blue berry packaged with 150mL glass. The total production of 600 packs / month with a selling price of Rp.4,000. IbKIK activities have successfully trained and fostered new entrepreneurs. as many as eight students joined in the KWU unit of the student association of the Department of Biology FMIPA UNP.